Produksi biocoal berbahan dasar tandan kosong kelapa sawit sebagai bahan bakar alternatif pada pembangkit listrik tenaga uap dengan metode torefaksi pada temperatur 200oC - Awaludin Martin; Yogie Rinaldy Ginting; Iwan Kurniawan; Andika; Dhiki R. A. (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
Coal fired steam power plants (CFSPP) are one of the industries that use fossil energy as a main fuel, causing fossil energy reserves are decreasing, for that the switchover of using fossil energy into new and renewable energy is necessary. To achieve the energy mix target, Indonesian Government through to Ministry of Energy and Mineral Resources was have the regulation to increasing the use of new and renewable energy through the co-firing method for steam power plants by utilizing biomass as a coal mixture. However, biomass from empty fruit bunches has several weaknesses as fuel and one of the weakness of empty fruit bunch is have a low heating value. Torrefaction method at 200oC is a method was use to increasing the heating value of biomass from empty fruit bunches. In previous research using the torrefaction method at a temperature of 200°C for 30 minutes obtained bio-coal with the highest mass yield and energy yield 78% and 96.11% with a heating value 4799.27 kcal/kg where the heating value is equivalent to the heating value of coal. This research is a continuation of previous research, where in the previous study the weight of sample of empty fruit bunch was only 1000 g, in this study the sample weight was varied up to 100 g with the same torrefaction method, namely with a temperature of 200°C and a torrefaction process time of 30 minutes using fixed bed reactor. The result of this research is bio-coal with the highest calorific value of fuel at 6,253 kcal/kg with a mass variation of 1000 g.